Survey of Interest in Learning Basketball in Ambon State Madrasah Aliyah - Yusuf Yusuf; J. Anaktototy; Emma Rumahlewang (International Journal of Education, Information Technology, and Others, 2023)
This study aims to determine students' interest in basketball at Madrasah Aliyah Negri Ambon. Interest is the most important problem in education when it is associated with one's activities in everyday life. Interest can be interpreted as a feeling of pleasure in dealing with an object. This research is a quantitative research with a survey approach with a questionnaire as a data collection tool. This research was carried out at the Ambon State Madrasah Aliyah with 45 students as samples. The sampling technique was carried out by purposive sampling (sample aims). According to Arikunto (2006), objective sampling is done by taking subjects not based on strata, random or region but based on having a specific purpose. The results of the study regarding students' interest in learning basketball at Ambon State Madrasah Aliyah were in the very low category of 7% or as many as 3 students, who were in the low category of 24% or as many as 11 students, who were in the medium category of 40% or as many as 18 students, who are in the high category of 20% or as many as 9 students and who are in the very high category of 9% or as many as 4 students.